Hydrodynamics and Tidal Turbine Generator Stability Analysis in Several Wave Variations. (16th June 2021) - Ikhwan, Muhammad; Rizal, Syamsul; Ramli, Marwan; Muchlisin, Zainal A.; Munzir, Said
Abstract : The development of tidal turbines continues to be carried out by many researchers, including the incorporation of a control system for optimization purposes. This paper attempts to assess the stability of two mechanical systems in a tidal turbine: a propeller harvesting kinetic energy and a d-q diagram system on a permanent-magnet synchronous generator (PMSG). The method employed is the representation of a phase plane profile with a stable eigenvalue. The critical value of the turbine's rotations per minute provides some points of equilibrium. The effect of the angular velocity singular on the modified system was also investigated. There is no cutoff control for the generator rotational speed in the case of weak currents, according to the results. The combination of the three tidal turbine components results in a shift in the equilibrium point. Although PMSG has an infinite equilibrium point along the line I d = 0, the effect of the rotor angular velocity prevents all of these points from being in equilibrium. Finally, in this study, the rotor angular velocity caused by the speed and type of ocean currents are only the upper and lower limits. The stability of the various wave variations is within this range.